VEGF expression and cell apoptosis in NOD mouse retina - Li, Cai-Rui (International Journal of Ophthalmology Press, 2010)
AIM: To investigate retinal vascular endothelial growth factor (VEGF) level and retinal cells apoptosis in the early stage of diabetic NOD mouse retina. METHODS: Animals were divided into non-diabetes group, (control) (2-, 4-, 6-, 8- and 12-week sub-groups, n=30) and diabetes group (2-, 4-, 6-, 8- and 12-week sub-groups, n=30). Enzyme-linked immunosorbent assay (ELISA) was performed to detect VEGF level in both serum and retina. Transmission electron microscope method was used to examine retinal cell apoptosis. RESULTS: Compared with the control group, VEGF levels in serum and retina were increased significantly in the NOD group (12 weeks: 4.9±0.4µg/g vs 0.19±0.1µg/g in serum sample, P<0.01; 165±9µg/g vs 17±5µg/g in retinal sample, P<0.01). There exists a positive correlation between serum VEGF and retinal VEGF levels in the early diabetic NOD mice (γ=0.9902, P=0.001). The number of the cells apoptosis in the ganglion cells and endothelium can also been found increased significantly in the NOD group (P<0.01). CONCLUSION: The high VEGF expression may be contributed to increased retinal cells apoptosis. Many factors associated with retinal VEGF expression might involve in the early diabetes stage.